2023
DOI: 10.3389/fped.2023.1070722
|View full text |Cite
|
Sign up to set email alerts
|

Childhood vaccination practices and associated factors among mothers/caregivers in Debre Tabor town, Northwest Ethiopia: A cross-sectional study

Abstract: BackgroundIncomplete immunization and non-immunization increase the risk of disease and death among children. This study aims to assess childhood vaccination practices and associated factors among mothers and caregivers in Debre Tabor town, Amhara region, Ethiopia.MethodsA community-based cross-sectional study design was conducted between February 30 and April 30, 2022. The study participants were proportionally allocated to all six kebeles found in the town. A systematic random sampling technique was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This was reflected in the literature that showed that private physicians recommend against receiving MoPH vaccines and advice parents to delay immunization due to financial barriers, even when available for free in PHCCs [4]. The lack of physician recommendation and reassurance intensifies the fear of side effects, both of which were major barriers against childhood immunization reported in our study and goes in line with available literature in Lebanon [7,13] and in the region on immunization, whether routine immunization [7,8,13,14] or influenza vaccine [15]. Physician recommendation was reported as the sole factor and most important player that overcomes misconceptions, vaccine hesitancy and fear of side effects in Lebanon [15].…”
Section: Discussionsupporting
confidence: 85%
“…This was reflected in the literature that showed that private physicians recommend against receiving MoPH vaccines and advice parents to delay immunization due to financial barriers, even when available for free in PHCCs [4]. The lack of physician recommendation and reassurance intensifies the fear of side effects, both of which were major barriers against childhood immunization reported in our study and goes in line with available literature in Lebanon [7,13] and in the region on immunization, whether routine immunization [7,8,13,14] or influenza vaccine [15]. Physician recommendation was reported as the sole factor and most important player that overcomes misconceptions, vaccine hesitancy and fear of side effects in Lebanon [15].…”
Section: Discussionsupporting
confidence: 85%
“…Mothers' knowledge, attitude, and practice play an important role in achieving complete immunisation before the first birthday of the child; previous parent factors are also contributing to the success or failure of immunization programs [19]. Also, knowledge, attitude, and practice studies provide information about the people's awareness of certain topics, their feelings, and their [20].…”
Section: ©Nijbas Open Access Publications 2024mentioning
confidence: 99%
“…Despite implementing different high-impact interventions to reach every child, a significant number of children have not completed their vaccination at the recommended age perhaps partly due to low maternal satisfaction. Even though there were studies on maternal satisfaction in the urban areas [ 1 ] and central areas of the agrarian community [ 11 , 12 , 33 , 37 , 38 ], there is a lack of evidence on client perspective from a pastoralist community, one being the rural and remote areas of Southern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%